KONSEP ECOPEDAGOGY DALAM PELESTARIAN KEARIFAN LOKAL DI MIN 10 BLITAR - Mohamad Sabilli Firmansyah; Agus Mukti Wibowo (Fakultas Studi Islam UNISKA MAB Banjarmasin, 2022)
Ecopedagogy is an academic movement to make students aware of being individuals who have understanding, awareness, and skills in protecting and preserving nature. The ecopedagogy concept is oriented towards a sustainable future or sustainability in preserving nature. By applying the ecopedagogy concept, it can make the school environment clean, beautiful, comfortable for learning and can bring up attitude of caring for the environment in students as a form of preserving local wisdom. This research explores the concept of ecopedagogy in the preservation of local wisdom at MIN 10 Blitar. The purpose of describe the ecopedagogy concept in the preservation of local wisdom at MIN 10 Blitar. This research uses a descriptive qualitative approach and the type of research is an instrumental case study. The data collection techniques in this research are observation, interview, and documentation. The data analysis technique of this research uses the Milles and Huberman model with three steps analysis: data reduction, data presentation, and conclusion. The results of this research indicate that the ecopedagogy concept at MIN 10 Blitar is implemented through a series of eco green programs. The ecopedagogy concept at MIN 10 Blitar, it can foster students to have ecological awareness and have skills to preserve the environment. Students of MIN 10 Blitar can play an active role in the preservation of local wisdom